Estimated incidence of influenza‐associated severe acute respiratory infections in Indonesia, 2013‐2016 - Susilarini, Ni K. (Influenza Other Respir Viruses, 2017)
BACKGROUND: Indonesia's hospital‐based Severe Acute Respiratory Infection (SARI) surveillance system, Surveilans Infeksi Saluran Pernafasan Akut Berat Indonesia (SIBI), was established in 2013. While respiratory illnesses such as SARI pose a significant problem, there are limited incidence‐based data on influenza disease burden in Indonesia. This study aimed to estimate the incidence of influenza‐associated SARI in Indonesia during 2013‐2016 at three existing SIBI surveillance sites. METHODS: From May 2013 to April 2016, inpatients from sentinel hospitals in three districts of Indonesia (Gunung Kidul, Balikpapan, Deli Serdang) were screened for SARI. Respiratory specimens were collected from eligible inpatients and screened for influenza viruses. Annual incidence rates were calculated using these SIBI‐enrolled influenza‐positive SARI cases as a numerator, with a denominator catchment population defined through hospital admission survey (HAS) to identify respiratory‐coded admissions by age to hospitals in the sentinel site districts. RESULTS: From May 2013 to April 2016, there were 1527 SARI cases enrolled, of whom 1392 (91%) had specimens tested and 199 (14%) were influenza‐positive. The overall estimated annual incidence of influenza‐associated SARI ranged from 13 to 19 per 100 000 population. Incidence was highest in children aged 0‐4 years (82‐114 per 100 000 population), followed by children 5‐14 years (22‐36 per 100 000 population). CONCLUSIONS: Incidence rates of influenza‐associated SARI in these districts indicate a substantial burden of influenza hospitalizations in young children in Indonesia. Further studies are needed to examine the influenza burden in other potential risk groups such as pregnant women and the elderly.